2011
DOI: 10.1007/s11845-010-0671-3
|View full text |Cite
|
Sign up to set email alerts
|

Caring for dementia carers: the role of general practitioners in Ireland

Abstract: Dementia carers form an important yet understated patient group who present unique challenges for general practitioners in Ireland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…In total, 23 papers were from the peer‐reviewed literature and four published by associations in the grey literature. Peer‐reviewed literature included the following: three papers reviewing the ethics of physicians engagement with caregivers (Barnard & Yaffe, ; Gitlin & Hodgson, ; Mitnick, Leffler, & Hood, ); three literature reviews on the role of physicians in care of the dementia caregivers (O'Connor, ; Robinson et al, ; Sunne & Huntington, ); a report on the development of a survey on physician's perceptions of care for caregivers (Bedard, Gibbons, Lambert‐Belanger, & Riendeau, ), a policy paper (Moore, Frank, & Chambers, ), 12 qualitative investigations (Burridge, Mitchell, Jiwa, & Girgis, ; Burridge, Mitchell, Jiwa, & Girgis, ; Carduff et al, ; Doekhie, Strating, Buljac‐Samardzic, Bovenkamp, & Paauwe, ; Foley, Boyle, Jennings, & Smithson, ; Gill et al, ; Greenwood, Mackenzie, Harris, Fenton, & Cloud, ; Hum et al, ; Kiceniuk et al, ND; Krug et al, ; Leu, Frech, & Jung, ; Wang et al, ); and three reports on two surveys (Greenwood, MacKenzie, Habibi, Atkins, & Jones, ; Jones, Mackenzie, Greenwood, Atkins, & Habibi, ; Thyrian & Hoffmann, ). A policy paper Doctors of BC ,), two guides to developing caregiver‐centred care practice (Doctors of BC ,; Princess Royal Trust, ), and a survey (Skufca, ) were published by organisations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 23 papers were from the peer‐reviewed literature and four published by associations in the grey literature. Peer‐reviewed literature included the following: three papers reviewing the ethics of physicians engagement with caregivers (Barnard & Yaffe, ; Gitlin & Hodgson, ; Mitnick, Leffler, & Hood, ); three literature reviews on the role of physicians in care of the dementia caregivers (O'Connor, ; Robinson et al, ; Sunne & Huntington, ); a report on the development of a survey on physician's perceptions of care for caregivers (Bedard, Gibbons, Lambert‐Belanger, & Riendeau, ), a policy paper (Moore, Frank, & Chambers, ), 12 qualitative investigations (Burridge, Mitchell, Jiwa, & Girgis, ; Burridge, Mitchell, Jiwa, & Girgis, ; Carduff et al, ; Doekhie, Strating, Buljac‐Samardzic, Bovenkamp, & Paauwe, ; Foley, Boyle, Jennings, & Smithson, ; Gill et al, ; Greenwood, Mackenzie, Harris, Fenton, & Cloud, ; Hum et al, ; Kiceniuk et al, ND; Krug et al, ; Leu, Frech, & Jung, ; Wang et al, ); and three reports on two surveys (Greenwood, MacKenzie, Habibi, Atkins, & Jones, ; Jones, Mackenzie, Greenwood, Atkins, & Habibi, ; Thyrian & Hoffmann, ). A policy paper Doctors of BC ,), two guides to developing caregiver‐centred care practice (Doctors of BC ,; Princess Royal Trust, ), and a survey (Skufca, ) were published by organisations.…”
Section: Resultsmentioning
confidence: 99%
“…The reimbursement for the time spent with caregivers may be inadequate, particularly if the caregiver is not the doctor's patient (Bedard et al, ; Burridge et al, , ; Carduff et al, ; Doctors of BC ,; Doekhie et al, ; Foley et al, ; Gill et al, ; Greenwood & Mackenzie, ; Greenwood et al, ; Hum et al, ; Jones et al, ; Kiceniuk et al, ND; Krug et al, ; Leu et al, ; O'Connor, ; Skufca, ; Sunne & Huntington, ; Thyrian & Hoffmann, ; Wang et al, ). To illustrate, in preliminary results from an ongoing Primary Care for Caregivers Study Kiceniuk et al (ND) reported that in Nova Scotia physicians cannot bill for time spent talking to caregiver unless the caregiver is a patient and had booked an appointment separately from the patient.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, however, as a consequence of the care situation, CGs frequently do not have time to seek medical advice for their own conditions. Here, the demented patients' physicians have, in addition to the actual patient's treatment, an important function in recognizing the negative impacts of caregiving on those providing the care (Adelman et al 2014;Cohen 2000;O'Connor 2011). While the physician's responsibility is naturally limited to health issues of the patient, he or she might still have a goodand in some cases perhaps the onlyopportunity to recognize and address mental health issues in the CGs arising from the care situation.…”
Section: Introductionmentioning
confidence: 99%